2019
DOI: 10.1038/s41598-019-48733-w
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble solids at high concentrations repress yeast’s response against stress and increase intracellular ROS levels

Abstract: Lignocellulosic ethanol production requires high substrate concentrations for its cost-competitiveness. This implies the presence of high concentrations of insoluble solids (IS) at the initial stages of the process, which may limit the fermentation performance of the corresponding microorganism. The presence of 40–60% IS (w/w) resulted in lower glucose consumption rates and reduced ethanol volumetric productivities of Saccharomyces cerevisiae F12. Yeast cells exposed to IS exhibited a wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…During lignocellulosic fermentation, both the substrate (for, e.g., xylose and biomass solids) and the end-product ethanol can induce stress in S. cerevisiae (Cunha et al 2019a;Moreno et al 2019;Osiro et al 2019). LCB is processed through pretreatment into a solid fraction composed of insoluble solids (IS), as well as a liquid fraction containing soluble sugars such as xylose.…”
Section: Substrate And/or End-product Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…During lignocellulosic fermentation, both the substrate (for, e.g., xylose and biomass solids) and the end-product ethanol can induce stress in S. cerevisiae (Cunha et al 2019a;Moreno et al 2019;Osiro et al 2019). LCB is processed through pretreatment into a solid fraction composed of insoluble solids (IS), as well as a liquid fraction containing soluble sugars such as xylose.…”
Section: Substrate And/or End-product Inhibitionmentioning
confidence: 99%
“…LCB is processed through pretreatment into a solid fraction composed of insoluble solids (IS), as well as a liquid fraction containing soluble sugars such as xylose. During fermentation, the solids can negatively interact with yeast, decreasing fermentation performance by (i) deforming cellular morphology, (ii) disrupting the plasma membrane, (iii) increasing ROS formation, and (iv) altering gene expression and negating cellular stress responses (Moreno et al 2019).…”
Section: Substrate And/or End-product Inhibitionmentioning
confidence: 99%
“…Authors of this dataset indicated that 200 genes were overexpressed and 513 genes were downregulated between insolublesolid (IS) cultures and ordinary cultures. Three biological repeats were used for both the IS cultures and ordinary cultures (Moreno, González‐Fernández, Ballesteros, & Tomás‐Pejó, 2019). The online tool GEO2R was used to reanalyze this dataset with default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Moreno et al evaluated the effects of high concentrations of IS on S. cerevisiae F12. In the presence of 40-60% IS (w/w), significantly lower glucose consumption and reduced ethanol production were observed (Moreno, González-Fernández, Ballesteros, & Tomás-Pejó, 2019). Furthermore, in the presence of IS, yeast cells exhibited a wrinkled surface, reduced cell size, and increased levels of reactive oxygen species (ROS).…”
Section: The Website Interface Of Yir/gslamentioning
confidence: 99%
See 1 more Smart Citation